Improved garment longevity and reduced microfibre release are important sustainability benefits of laundering in colder and quicker washing machine cycles. (June 2020) - Cotton, Lucy; Hayward, Adam S.; Lant, Neil J.; Blackburn, Richard S.
Abstract: The global impact of laundering clothing is significant, with high levels of water, energy use, and pollution associated with this consumer care process. In this research, the impacts of washing temperature and washing time on garment colour loss (dye fading), colour transfer (dye staining), and microfibre release were evaluated using retail consumer clothing. Significantly greater colour loss and greater colour transfer were observed for a 40 °C, 85 min wash cycle compared to a cold-quick (25 °C; 30 min) cycle. Desorbing dyes were found to mainly be reactive dyes. From fundamental kinetic studies, it was observed that significant increases in both rate of dye desorption and total dye desorption occurred when increasing from 20 °C to 40 °C, but the difference in dye release between 40 °C and 60 °C was not as significant; the same kinetic trends were observed for dye transfer. Microfibre release was significantly greater for the 40 °C, 85 min cycle in comparison with the cold-quick cycle, and this effect continued with further washes. These results mean that reducing time and temperature in laundry could have a significant impact in terms of extended garment longevity and reduced dye and microfibre liberation into the environment, in addition to energy savings. Highlights: More colour loss occurred in 'warmer-longer' wash cycles than 'cold-quick' cycles. Rate of dye desorption increases most significantly between 20 °C and 40 °C. Microfibre release much higher in 40 °C, 85 min cycle compared to cold-quick. Microfibre release is still significant after 16 washes. Reducing time and temperature in laundry could have major environmental benefits.